Perbandingan Uji Kadar Vitamin C Dan Antioksidan Buah Jambu Biji Merah (Psidium guajava L.,) Segar dan Dalam Kemasan Menggunakan Metode DPPH Di Kecamatan Marbau - Rahmayani Hasibuan; Rahmadina; M. Idris (Jurnal Biologi dan Pembelajarannya (JB&P), 2024)
Red guava (Psidium guajava L.) has antioxidants that can prevent or inhibit the oxidation process inhibit the oxidation process. The purpose of the study was to determine the amount of comparison the highest vitamin C and antioxidant levels between fresh red guava and packaged red guava. red guava fruit in packaging. The research method used was quantitative quantitative method by free radicals DPPH (Diphenyl Picrylhydrazyl). The results of the study found that fresh red guava vitamin C guava has a level of 0.70 mg/100 grams higher than the packaged vitamin C of 0.43 mg/100 grams packaged at 0.43 mg/100 grams. IC50 value of red guava value of 194.22 ppm which is categorized as moderate, while the IC50 value in the packaging 516.59 ppm is categorized as very weak.